PERANAN LUMBUNG PANGAN DAN PENGGILINGAN PADI DALAM MENDUKUNG PEMBIAYAAN USAHATANI DI SUMATERA SELATAN - Hutapea, Yanter; , Hermanto (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2008)
The Role of Rice Barn and Rice Milling Unit to Support farming Finance in South Sumatera. The aimed of this assessment was to know: 1) The performance of rice barn and rice milling unit (RMU) to serve farmer 2) the farmers accessibility to rice barn and RMU. Survey was conducted from March to May 2006 in 8 regencies (OKI, OKU Timur, OKU Selatan, Muara Enim, Lahat, Musi Rawas, Musi Banyuasin dan Banyuasin). Data were collected by interviewing 19 members of rice barn, 25 customers of RMU, 14 rice barn leaders and 21 RMU owners. The result of this assessment showed that the scarcity of capital faced by the farmer household generally in order to develop their farming. The financial institute such as rice barn and RMU in rural areas could be accessed by the farmer to get the operational cost of farming. The average of cash money of rice barn and RMU with magnitude of Rp.25.329.880 dan Rp.46.483.300, respectively. The amount of rice barn have credits and debts with magnitude of 35,71% and 14,28% respectively. Meanwhile, RMU have credits and debts with magnitude of 38,09% and 9,52% respectively. Many of Rice barn and RMU have post-harvest and ploughing facilities, input production supply, besides lending the money that used for production cost. The owner of RMU appear to help farmer easily, nevertheless many of them were not able to fulfill the farmer needs. Rice barn institutes developed by government was not available yet to lend the financial capital for the farmer. Key words : Rice barn, rice milling unit, farmer accessibilityPengkajian ini bertujuan untuk mengetahui: 1) keragaan lembaga lumbung pangan dan penggilingan padi dalam melayani kebutuhan petani 2) aksesibilitas petani terhadap lembaga lumbung pangan dan penggilingan padi. Survei dilakukan pada bulan Maret sampai Mei 2006 di 8 kabupaten (OKI, OKU Timur, OKU Selatan, Muara Enim, Lahat, Musi Rawas, Musi Banyuasin dan Banyuasin). Data dikumpulkan dengan mewawancarai 19 orang petani anggota lumbung pangan, 25 orang petani pelanggan penggilingan padi, 14 orang pengelola lumbung pangan dan 21 orang pemilik penggilingan padi. Hasil kajian menunjukkan bahwa rumah tangga petani umumnya mengalami masalah keterbatasan modal dalam mengembangkan usahataninya. Lumbung pangan dan penggilingan padi merupakan lembaga ekonomi di perdesaan yang diakses petani untuk mendapatkan modal. Modal tunai rata-rata pada lembaga lumbung pangan dan penggilingan masing-masing sebesar Rp.25.329.880 dan Rp.46.483.300. Sebanyak 35,71% lumbung memiliki piutang dan 14,28% memiliki hutang. Sedangkan penggilingan padi, sebanyak 38,09% memiliki piutang dan 9,52% memiliki hutang. Beberapa di antara lumbung dan pengilingan padi juga memiliki fasilitas untuk pengeringan gabah, pengolahan lahan dan penyediaan sarana produksi selain menyediakan modal untuk biaya produksi usahatani. Pemilik penggilingan padi sering tampil sebagai penolong dengan kemudahan yang diberikannya, meskipun belum semuanya mampu melayani kebutuhan petani. Lumbung pangan sebagai lembaga ekonomi yang dibentuk pemerintah belum mampu berperan penuh dalam melayani kebutuhan petani.Kata kunci: Lumbung pangan, penggilingan padi, aksesibilitas petani